Coastal zones of the Red river delta and Yangtze river delta - Vinh, Vu Duy; Hai, Nguyen Minh (Vietnam Journal of Marine Science and Technology, 2020)
The Red river delta coastal area (Vietnam) and Yangtze river delta coastal area (China) not only play an important role in developmental process of each country but also show typical characteristics of hydrodynamics and sediment dynamics of estuaries and delta coastal areas. Based on previous studied results of hydro-sediment dynamics in two delta coastal zones that were published, this paper gives a comparison of hydrodynamics and sediment dynamics of the coastal zones of Red river and Yangtze river. The results showed that there are some similar features of these two regions such as riverine hydrology, decreased fluvial sediment flux due to the dam, grain size of suspended sediment, alongshore sediment and morphological change. Besides, these two regions also have some distinct characteristics such as tidal regime and residual field currents.